2010
DOI: 10.2478/s11687-010-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ribosomal internal transcribed spacer 2 (ITS2) interspecific markers in Fasciola hepatica, Fascioloides magna, Dicrocoelium dendriticum and Paramphistomum cervi (Trematoda), parasites of wild and domestic ruminants

Abstract: 76 SummaryThe species-specific ribosomal internal transcribed spacer 2 (ITS2) markers were designed for PCR-based molecular differentiation of Fasciola hepatica, Fascioloides magna, Dicrocoelium dendriticum and Paramphistomum cervi, liver and stomach flukes of domestic and free living ruminants. Complete ITS2 sequences were obtained for D. dendriticum and P. cervi, for the later species, ITS2 structure was determined for the first time. Intraspecific variation within geographically distant populations was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…The parasites were identified based on the sequence of the internal transcribed region 2 (ITS-2) with the use of primers designed by Wobeser and Schumann (23), Kralova-Hromadova et al (9), and Bazsalovicsova et al (2). A PCR method was used, as described by Kasny et al (7) with some modifications concerning reaction mixture and the time of amplification conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The parasites were identified based on the sequence of the internal transcribed region 2 (ITS-2) with the use of primers designed by Wobeser and Schumann (23), Kralova-Hromadova et al (9), and Bazsalovicsova et al (2). A PCR method was used, as described by Kasny et al (7) with some modifications concerning reaction mixture and the time of amplification conditions.…”
Section: Methodsmentioning
confidence: 99%
“…2). The PCR products were of corresponding size as amplicons obtained on genomic DNA isolated from adult flukes (Bazsalovicsová et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of the method was checked microscopically and followed by the amplification of egg DNA using ribosomal internal transcribed spacer 2 (ITS2) species-specific primers. Intraspecific variation within the ITS2 region has recently been evaluated in worldwide geographic populations of all four flukes (Králová-Hromadová et al, 2008;Bazsalovicsová et al, 2010). The studies revealed low (F. hepatica, D. dendriticum) or no (F. magna, P. cervi) intraspecific variation and consistent interspecific differences amongst the four liver and stomach flukes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations